Influence of supplementation of wheat straw based total mixed ration with saponins on total gas and methane production in vitro - MALIK, P K; SINGHAL, K K (The Indian Journal of Animal Sciences, 2011)
Effect of supplementation of total mixed ration (wheat straw and concentrate, 60 : 40) with con1mercial grade saponins at different levels [0 (So), 1 (S1)’ 2 (S2) and 4(84) %] on production of total gas and n1ethane during enteric fennentation was studied in vitro. Total gas production (llkg DM) in treatments S2 (141.75) and S4 (156.20) was significantly higher than that in treatments So (111.90) and S1 (115.50). Average methane and protozoal counts decreased gradually on increasing the levels of saponins in the ration and maximum reduction in methane (29%) and protozoal counts in incubation (62%) was recorded at S41evel as compared to the control. The decrease in methane production in treatments S2 and S4 was lower than in control (So) and SI however, IVDMD did not vary significantly an10ng the treatn1ents. TVFA concentration in treatments So’ Sb S2 and S4 was 97.30, 99.60, 100.27 and 98.25 mlnoles/litre respectively, and variation amongst the treatments was not significant. Molar proportion of propionate increased at the expense of acetate following the saponins supplementation particularly in treatment S4. Proportion of butyrate in incubation medium remained unaffected by the levels of saponins in total mixed ration. Thus, saponins supplementation at 2 and 4% to the total mixed ration can increase total gas production and decrease methane production due to the adverse effect on protozoal numbers in rumen without affecting DM digestibility. These observations indicated that dietary inclusion of saponins containing feeds or herbs may have potential for mitigating the methane emission during enteric fennentation in ruminants. Â